Intravitrealversus Posterior Subtenon Triamcinolone Acetonide in Conjunction with Intravitreal Bevacizumab for Refractory Diabetic Macular Edema: DOI: 10.36351/pjo.v38i3.1400 - Gull, Ambreen; Khan Niazi, Fuad Ahmad; Raza, Ali (Pakistan Journal of Ophthalmology, 2022)
Purpose Aim of this study was to evaluate and compare the effects of combined simultaneous injection of intravitreal triamcinolone acetonide and bevacizumab versus intravitreal bevacizumab and posterior subtenon triamcinolone acetonide in treatment of persistent refractory diabetic macular edema after intravitreal bevacizumab injection failure Methods 40 pseudophakic diabetic patients were enrolled in quasi experimental study conducted at ophthalmology department. All eyes were specifically diagnosed with persistent refractory diabetic macular edema with central retinal thickness of _____on OCT. Patients were divided into two groups. Group A was given simultaneous injection of intravitreal bevacizumab 1.25mg/0.05ml with posterior subtenon triamcinolone 40mg and group B was given intravitreal bevacizumab in conjunction with simultaneous intravitreal triamcinolone 2mg/0.05 ml.Patients were followed upmonthly till three months. Changes in the best corrected visual acuity, intraocular pressure and central retinal thickness by optical coherence tomography were evaluated in both groups. Retreatment was given at 12 weeks interval whenever indicated by OCT. Results Group B showed a more significant decrease in the median CRT at 1month (p =0.0002)but after 3 months both groups showed a reduction in CRT which was not statistically significant between two groups _____. Both groups had significant improvement in BCVA compared to pre-injection baseline visual acuity.Between two groups BCVA changes were not statistically significant at 3 months _____.Five eyes in group B developed IOP beyond 22mmHg, which was treated with anti glaucoma medications within 2 weeks. No eye in group A developed IOP greater than 21mmHg. At 12 weeks, 7 of group A patients and 6 of group B patients developed recurrent macular edema and required repeated injections. Conclusion While treating persistent refractory diabetic macular edema, posterior subtenon triamcinolone is as effective as intravitreal triamcinolone in conjunction with intravitreal bevacizumab in reducing CRT and improving and stabilizing BCVA but in terms of IOP rise posterior subtenon injection is safer as compared to intravitreal injection. Both treatments are cost effective and combined simultaneous injections decrease the number of repeated injections.